The New Growth Theories and Their Empirics after Twenty Years - Rosa Capolupo (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
In this work the author updates the reviews on endogenous growth theories in order to explore whether recent empirical studies have become more supportive of their main predictions. Among the core topics studied in the growth econometric framework, namely convergence, identification of growth determinants and factors responsible for growth differences in the data, the primary focus of this paper is on the last two. The author will review, from macro growth regressions, studies that test primarily the performance of endogenous models in terms of significance and robustness of the coefficients of growth determinants. By highlighting methodological issues and critical discussion, she argues that: (i) causal inference drawn from the empirical growth literature remains highly questionable, (ii) there are estimates for a wide range of potential factors but their magnitude and robustness are still under debate. Her conclusion, however, is that, if properly interpreted, the predictions of endogenous growth models are gathering increasing empirical support.
Keywords: O47; O41; C31; 330; Endogenous growth; growth regressions; convergence; Neue Wachstumstheorie; Entwicklungskonvergenz; Schätzung; Theorie; Welt